(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Despite the emphasis on preventing pressure injuries (PI) in emergency rooms, pressure injuries acquired in the hospital still happen in these types of environments. To systematically compile the research on the most efficient nursing treatments for preventing pressure injuries in critical care patients. A systematic search was conducted across four electronic databases to identify relevant research. The studies that were included underwent a screening process and were subsequently evaluated utilizing the suitable Joanna Briggs Institute rating technique. The data were analyzed and published using an analytical narrative methodology. Nurses possess the necessary qualifications to assume leadership roles in avoiding the occurrence of injuries due to pressure in emergency rooms. Each patient who is critically sick needs actions to avert pressure injuries, and the avoidance of PIs should be seen as a multifaceted strategy. Nurses are required to strategize and execute evidence-based treatment in order to avoid many forms of pressure injuries, such as those caused by medical devices. Education and training programs focused on pressure injury prevention are crucial for nurses to effectively avoid pressure injuries. Nursing interventions should be founded on evidence and organized into cohesive sets of actions, known as ’bundles’, which may be tailored to meet the specific requirements of individual patients. In order to minimize pressure injuries in critically sick patients, nurses must possess a high level of competence and education. They should also consistently follow essential measures to enhance movement and relieve pressure.